폴리올(글리세린과 알칸디올)의 특성에 따른 비타민 C 갈변 현상 비교 - 서재형; Jae Hyeong Seo; 최진우; Jin Woo Choi; 노호식; Ho Sik Rho (大韓化粧品學會誌, 2025)
폴리올은 화장품에서 주로 보습제, 피부 컨디셔닝제로 사용되는 원료로서, 비타민C 화장품에서 안정도를 향상시키기 위해 사용하는 대표적인 물질이다. 이는 폴리올이 비타민 C와 수소결합을 형성하여 물 분자 사이의 상호작용 및 산소와의 접촉을 방해하기 때문이라고 알려져 있으며, 이와 관련하여 다양한 연구가 진행되었다. 수소 결합은 분자의 특성(탄소체인 길이, 히드록시 위치)에 따라 달라질 수 있으며 이에 관한 구조적인 연구가 필요한 실정이다. 하지만 대부분의 연구가 글리세린, 1,3-프로판다이올 및 1,3-부탄다이올에 관한 연구이며, 폴리올의 구조적 특성이 비타민 C의 변색에 미치는 영향에 대해서 체계적으로 진행된 연구는 없다. 따라서 폴리올의 길이(C 2 -C 6 ), 폴리올의 히드록시 위치에 따른 비타민 C의 갈변 정도를 측정하는 실험을 진행하였다. 실험 결과, 비타민 C의 변색은 탄소체인의 길이가 길어질수록 변색이 증가하였으며, 특히 1,2-펜탄다이올과 1,2-헥산다이올에서 대조군보다 좋지 않은 변색 결과를 나타냈다. 또한 히드록시의 위치에 대해서는 1,2-알칸디올의 경우, 다른 알칸디올 보다 높은 변색 정도를 나타내는 것으로 확인되었다. 이러한 결과는 자유 수분 활동도를 나타내는 ‘수분 활성도(Aw)’와 관련성이 있는 것으로 판단된다. Polyols are raw materials used in cosmetics, primarily as moisturizers and skin conditioning agents, and are a common substance used to improve the stability of vitamin C in cosmetics. This is believed to be due to the polyols forming hydrogen bonds with vitamin C, preventing vitamin C from contacting water molecules and oxygen, and various studies have been conducted in this regard. The formation of hydrogen bonds may vary depending on the characteristics of the molecules, such as carbon chain length and hydroxyl group positions, necessitating structural research on these factors. However, most research has focused on glycerin, 1,3-propanediol, and 1,3-butanediol, with no systematic studies examining the discoloration of vitamin C based on the structural properties of polyols. Therefore, this study measured the degree of browning in vitamin C as a function of the Carbon chain length of polyol (C 2 -C 6 ) and the positions of the hydroxyl groups of polyol. The experimental results showed that as the carbon chain length increased, the browning of vitamin C also intensified, with 1, 2-pentanediol and 1, 2-hexanediol exhibiting greater browning than the control. Furthermore, in terms of hydroxyl group positioning, 1, 2-alkanediols demonstrated higher browning effect compared to 1, n-alkanediols. These results are likely related to water activity (Aw), which indicates the free water activity.